In vivo autophagy quantification: Measuring LC3 and P62 puncta in 3D image system from zebrafish larvae. Issue 10 (10th June 2021) - Elbialy, Abdalla
Abstract: Autophagy is a central pathway in maintaining cellular homeostasis through the recycling of damaged proteins and organelles. Detection of LC3 protein levels by immunofluorescence or western blot analysis is one of the most common ways to measure autophagy. For quantitative autophagy analysis, LC3 western blot analysis is commonly used, whereas immunostaining is used for qualitative autophagy analysis. However, zebrafish larvae have a lot of proteases that rapidly degrade LC3 protein in samples. P62 is another autophagy marker that bind to damaged proteins and can reflects autophagic status. This study demonstrates a fast and accurate way to quantify autophagy from LC3 and/or P62 immunostaining images. We used a three‐dimensional analysis of whole‐mount LC3 immunostaining images of zebrafish larvae. Counting LC3 and P62 punctate by two dimensions can be used as a qualitative method for the analysis of autophagy. However, here we demonstrate that 3D image analysis can be used as a quantitative, rapid tool for monitoring autophagy in zebrafish larvae and avoiding drawbacks of LC3 western blot analysis.